A similarity assessment method for discovering and adapting business services. (11th November 2010) - D'Ulizia, Arianna; Ferri, Fernando; Grifoni, Patrizia
The advent and achievement of new mobile technologies makes it possible to offer online services to people whenever and wherever they are. Location-based services, in particular, concentrate on providing users with information about points of interest or on the support for navigation and routing tasks. One of the main challenges for these services is to adapt information to be retrieved to the user, taking into account user's preferences and contextual data (e.g., time, user's location, weather, etc.). This paper focuses on such challenging issues, proposing a context-aware discovery process that is based on two kinds of similarities (semantic and structural) to facilitate the identification of semantically related services and to make the user's request more precise and selective.